Welsh Responses to the French Revolution : Press and Public Discourse, 1789-1802. - Löffler, Marion (Wales and the French Revolution., 2012)
This ground-breaking anthology presents loyalist and radical poetry and prose from the newspapers, almanacs and periodicals current in Wales from the outbreak of the French Revolution in1789 to the Peace of Amiens in 1802, together with an extended introduction and two maps.